Persistency of milk yield in Anglo Nubia x Criolla goats - Pesántez, Manuel; Hernández, Arelis; Fraga, Luis M. (Cuban Journal of Agricultural Science, 2016)
A study was made using 6 140 milk yield records on the test day, from ten fortnightly milk test recordings of 631 lactations corresponding to 383 Anglo Nubia x Criolla goats located in six herds in Loja, Ecuador, during the period from 2011 to 2013. The purpose was to determine the non-genetic factors affecting lactation persistency and to estimate their correlation with total milk yield, milk yield adjusted to 152 d and lactation length. A linear, mixed generalized model was applied through the GLIMMIX procedure of SAS. As fixed effect were considered the herd, kidding year, season, number of lactation and youngs. Lactation length was considered as linear covariable and the random effect was associated with each goat dwelling in the herd. For estimating Pearson’s correlations, the CORR procedure of SAS was applied. Persistency was of 69.4 %. The non-genetic factors were significant, except for litter size. The phenotypic correlations of total milk persistency, adjusted milk and lactation length were 0.20, 0.16 and 0.14, respectively. It is concluded that lactation persistency had a low phenotypic correlation regarding milk yield and lactation length. Further investigations should be conducted with greater numberof samples and genealogical information for recommending its inclusion in genetic breeding programs.Key words: goats, persistency, lactation, correlation, crossing